MODERNITY AND MENTAL HEALTH: DOES TECHNOLOGY MATTER? - Ramlan Mustapha; Siti Norma Aisyah Malkan; Tengku Nazatul Shima Tengku Paris, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
This comprehensive review explores the complex relationship between modernity, particularly technology, and mental health. It examines mental health disorders' prevalence and impact, aetiology, and current treatment approaches. The article then delves into the specific effects of technology on mental well-being, discussing the potential benefits and risks associated with our increasingly digital world. The review concludes by emphasising the need for a balanced approach that leverages the benefits of technology while mitigating its potential harms. It also highlights areas for further research, including longitudinal studies on the long-term impacts of technology use on mental health and the development of evidence-based digital mental health solutions. This article provides a comprehensive overview of the current state of mental health in the context of modern technology, offering insights for researchers, healthcare professionals, and individuals seeking to understand and navigate this complex landscape.